Interpretation of the Koran in the Koran (lights and balance statement): comparative study - Al-Azzawi, Shaker Mahmoud Mahdi (Al-Adab Journal, 2020)
Praise be to God, Lord of the worlds, and prayers and peace be upon our master Muhammad and upon the good and pure God. The research is a statement of the method of the modernists in the interpretation of the Qur’anic text, and a statement that this approach is one of the precious approaches in the mind and has great tendencies and inaccuracies as these readings seek to empty the text of its content, and it violates the rules General through which we understand the Holy Quran. research aims: Clarify the correct position to deal with the Quranic text. Criticism of modernist approaches in dealing with texts. Show that these readings have a negative impact on the nation’s reality.